Differential relationships between discount rates and health behaviors in an ethnically diverse college sample - Natashia Bibriescas; Katherine Wainwright; Rebecca Thomas; Victoria Lopez; Paul Romanowich (Frontiers Media S.A., 2022)
Previous research has demonstrated associations between delay discount rate and engagement in several health behaviors. The delay discount rate is also inversely associated with social discount rates, a putative measure for sharing. However, there is little research that examines whether delay and social discount rates are differentially associated with health behavior engagement, and even less research examining the impact of ethnicity on these relationships. This study investigated whether delay and/or social discount rates predict three health behaviors varying in sociality: sexually transmitted infection (STI) testing, alcohol consumption and exercise frequency in an ethnically diverse university sample. The results showed that neither delay nor social discount rate significantly predicted alcohol consumption and exercise frequency. However, increasing social discount rates (i.e., decreased sharing) was associated with a decreased likelihood to be tested for STIs. Ethnicity significantly contributed to two models, indicating differences in STI testing and alcohol consumption across ethnicities. Ethnic differences in these health behaviors were consistent with many previous health behavior studies, suggesting a profitable way to research cultural contingencies and test the reliability of the ethnically diverse data. These findings indicate that the social discount rate is differentially associated with health behaviors with more social aspects (i.e., health behaviors related to sex) in college students.